2017
DOI: 10.1186/s13104-017-2580-2
|View full text |Cite
|
Sign up to set email alerts
|

Determinants and time to blood transfusion among thermal burn patients admitted to Mulago Hospital

Abstract: BackgroundBlood transfusion, a practice under re-evaluation in general, remains common among thermal burn patients due to the hematological alterations associated with burns that manifest as anemia. Today advocacy is for restrictive blood transfusion taking into account individual patient characteristics. We went out to identify the parameters that may determine transfusion requirement and the time to blood transfusion for thermal burn patients in Mulago Hospital in order to build statistics and a basis to sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 27 publications
0
17
1
Order By: Relevance
“…A multicenter retrospective study in a mixed population of adults and children with burn injury found that 75% of patients with TBSA > 20% received blood transfusion [ 20 ]. Another observational study evaluating predictive factors for blood transfusion in adults and children found TBSA > 20% is a useful predictor for blood transfusion [ 21 ]. Only few data are available to evaluate the association between TBSA and transfusion in an exclusively pediatric collective study like ours.…”
Section: Discussionmentioning
confidence: 99%
“…A multicenter retrospective study in a mixed population of adults and children with burn injury found that 75% of patients with TBSA > 20% received blood transfusion [ 20 ]. Another observational study evaluating predictive factors for blood transfusion in adults and children found TBSA > 20% is a useful predictor for blood transfusion [ 21 ]. Only few data are available to evaluate the association between TBSA and transfusion in an exclusively pediatric collective study like ours.…”
Section: Discussionmentioning
confidence: 99%
“…With the far-reaching impacts of injuries in LMICs [ 1-5 , 29 ] and the limited available research from these settings, additional study of blood product therapies, which are key to combating injury-related mortality, is crucial for informing clinical practice and policy. [42] 3, 5 Low Javali (2017) [43] 3 Moderate Kilyewala (2017) [57] 3, 4, 5 Very Low London (2001) [41] 2, 4 Low Mofidi (2010) [47] 2, 4, 5 Very Low Musau (2006) [50] 3, 4 Low Newton (2015) [51] 1, 3, 4, 5 Very Low Otieno (2004) [52] 3, 4 Low Sadeghi (2017) [48] 2, 3 Low Saidi (2014) [53] 3, 5 Low Sokhal (2017) [44] 3, 5 Low Srikant (2003) [45] 1, 3, 4 Very Low Tavousi (2018) [49] 3, 5 Low Yanar (2008) [56] 3 There is substantial research, including well-performed RCTs from HICs, that has led to development of consensus guidelines on the use of blood products in the treatment of acute injuries [ 14-16 , 18 , 59 , 60 ] [ 8 , 18 , 61 , 62 ]. Even though the global burden of injuries lies predominantly in LMICs [ 1-5 , 29 ], this systematic review demonstrates that there is a paucity of high-quality research from these settings.…”
Section: Discussionmentioning
confidence: 99%
“…Included reports were derived from Ghana (1) [41] , India (4) [42][43][44][45] , Iran (4) [46][47][48][49] , Kenya (4) [50][51][52][53] , South Africa (2) [ 54 , 55 ], Turkey (1) [56] and Uganda (1) [57] . The cumulative number of patients studied in all reports was 6535.…”
Section: Characteristics Of Included Reportsmentioning
confidence: 99%
“…Therefore, usually, large amounts of blood are required to prevent impaired erythropoiesis and serious blood loss. Other factors, such as a burn greater than 20% of the TBSA, a low BMI status, and abnormal white blood cell counts, might be potential indicators during consideration for blood transfusion [ 139 ]. Tavousi et al showed that, in a group of 701 burn patients, the mortality rate was two times higher among patients who had received blood transfusions compared to groups that were not treated with any blood products [ 140 ].…”
Section: Human Immunodeficiency Virusmentioning
confidence: 99%